CDKN2A Unclassified Variants in Familial Malignant Melanoma: Combining Functional and Computational Approaches for Their Assessment. Issue 7 (21st May 2014) - Scaini, Maria Chiara; Minervini, Giovanni; Elefanti, Lisa; Ghiorzo, Paola; Pastorino, Lorenza; Tognazzo, Silvia; Agata, Simona; Quaggio, Monica; Zullato, Daniela; Bianchi‐Scarrà, Giovanna; Montagna, Marco; D'Andrea, Emma; et al.
<x xml:space="preserve">Abstract</x> Our work tested an integrated model for the characterization of p16INK4a unclassified variants providing a robust tool for the interpretation of their structural and functional impact. We assessed the ability of new in silico tools to discriminate neutral/deleterious p16INK4a variants; combined in silico/in vitro assays; used a Bayesian method to obtain a final classification Evaluation of in silico/functional data disclosed a high agreement for 15/16 variants, suggesting that this approach could represent a pilot study. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>